STUDI KOMPUTASI REAKSI PENGGANDENGAN-SILANG SUZUKI-MIYAURA MENGGUNAKAN KATALIS PALADIUM DAN NIKEL - Roikhatul Jannah, Laila
The cross-coupling reaction of Suzuki and Miyaura is an organic reaction used to produce carbon-carbon bonds. This reaction can be used to produce biphenyls required for the chemical industry, agricultural products, pharmaceuticals, and biochemistry. This reaction involves halobenzene, which can react with organoboron compounds using transition metal catalysts such as palladium and nickel. Development of the mechanism for the Suzuki-Miyaura cross-coupling reaction using palladium and nickel single-atom catalysts to synthesize biphenyls. The use of single-atom catalysts to determine catalytic activity with the goal of reducing production costs and ligands can reduce toxicity. In addition to understanding the catalytic activity of nickel and palladium single-atom catalysts, it is necessary to comprehend the catalytic activity of other single-atom catalysts. For computational studies of this reaction, phenyl chloride and phenyl boronic acid are used as substrates. The use of phenyl chloride because it is more accessible and friendly to the environment. Using ORCA 5.0.2 software, computational studies were conducted by calculating Density Functional Theory (DFT). This study employs the Becke, 3-parameter, Lee–Yang–Parr (B3LYP) functional theory with D4 dispersion correction and DEF2-TZVP basis set. Using the Multiwfn program and the Tamm-Dancoff approximation (TDA), the charge transfer is computed using the Electrostatic Potential (ESP) charge and the HOMO-LUMO calculation. Computational calculations on the reaction will be visualized using Chemcraft. The mechanism of the Suzuki-Miyaura reaction involves three steps: oxidative addition, transmetalation, and reductive elimination. The results of the analysis at the oxidative addition stage correspond to the initial stage of the Suzuki mechanism for cross-coupling, in which phenyl chloride binds to a palladium or nickel catalyst, causing the chloride to separate from the phenyl. The palladium catalyst's activation energy was 34.68 kJ/mol, while Nickel's was 24.24 kJ/mol. Termination of the C-Cl bond on phenyl chloride requires charge transfer from the catalyst to phenyl chloride for a Palladium catalyst with 0.263e and a Nickel catalyst with 0.306e. The second step, transmetalation, begins with the addition of negatively charged phenyl trihydroxyboronate to Ph-M-Cl. In order for phenyl trihydroxyboronate to coordinate with Pd-Ph and Ni-Ph. Boric acid will be liberated to produce Ph-PdPh in the transition state. Using a single-atom Palladium catalyst, the activation energy for the release of boric acid from phenyl trihydroxyboronic is 74.17 kJ/mol, while Nickel's activation energy is 65.50 kJ/mol. The transfer of charge from boric acid to the Pd or Ni complex results in a charge transfer of 0.330e between boric acid and the palladium complex and 0.333e between boric acid and the nickel complex. The third step of the mechanism is reductive elimination, which begins with the decomposition of boric acid as a transmetalation product. This step illustrates the formation of a carbon-carbon bond that yields a biphenyl product. The occurrence of C-C interactions revealed that the activation energy of the Nickel catalyst was 51.73 kJ/mol compared to 42.48 kJ/mol for the Palladium catalyst. The charge on the Nickel catalyst becomes negative, resulting in a charge transfer of 0.186 e from biphenyl to the Nickel catalyst. The charge transfer from biphenyl to Palladium is 0.2790e. The transmetalation step determines the rate of the Suzuki-Miyaura cross-coupling reaction that forms carbon-carbon bonds in biphenyls. Calculation results indicate that during the oxidative addition and transmetalation stages, the nickel catalyst is superior to the palladium catalyst, whereas the palladium catalyst is superior during the reductive elimination stage. The mechanism of the Suzuki-Miyaura cross-coupling reaction demonstrates that a single nickel atom can substitute for palladium in the synthesis of biphenyls